MENCIPTAKAN LINGKUNGAN SEKOLAH AMAN TANPA PERUNDUNGAN DAN GROOMING - Robiatul Adawiyah; Aries Dirgayunita; Ulil Hidayah; Imro Atus Soliha (DEVELOPMENT: Journal of Community Engagement, 2023)
The social phenomenon that describes the many cases that occur in society, such as acts of bullying, is now increasingly felt and even results in fatalities. Ironically, this happens to many teenagers who are still in school. Bullying is any form of oppression or violence that is carried out intentionally by one person or group of people who are stronger or more powerful towards another person, with the aim of causing harm and is carried out continuously. Deepening material and socialization to teenagers on how to create a safe school environment without bullying or bullying and grooming. The reason for choosing the subject is Teenagers at the junior high school level are teenagers who are entering a period of transition between childhood and adulthood. At that age, cases of bullying that occur between friends are prone to occur. The impact of the changes that have occurred is that schools are able to create a safe school environment without bullying or bullying, both categories of mild, moderate and severe bullying cases.Keyword: School Environment, Bulliying, Grooming